If Only Forever (The Inn at Sunset Harbor-Book 4) - Sophie, Love (Lukeman Literary, 2017)
"Sophie Love's ability to impart magic to her readers is exquisitely wrought in powerfully evocative phrases and descriptions....This is the perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads." --Midwest Book Review (Diane Donovan re For Now and Forever) IF ONLY FOREVER is book #4 in the bestselling romance series The Inn at Sunset Harbor, which begins with book #1, For Now and Forever-a free download! 35 year old Emily Mitchell has fled her job, apartment and ex-boyfriend in New York City for her father's historic, abandoned home on the coast of Maine, needing a change in her life and determined to make it a B&B. She had never expected, though, that her relationship with its caretaker, Daniel, would turn her life on its head. Emily is still reeling from Daniel's proposal. As all seems to finally fall into place in her life, she looks forward to an exciting engagement year ahead, from shopping for a venue and a wedding dress, to creating her invite list, to setting a date. But all does not goes as planned. The endless events of the engagement year add more stress than joy, putting pressure on their relationship as they are forced to make hard choices. Adjusting to life as parents doesn't make it any easier, as Chantelle runs into problems at school and as a custody battle looms over them. As Christmas and New Years approach, the stress is only compounded. Meanwhile, as the B&B adds new guests and staff and as they find more priceless antiques, Emily discovers a shocking secret that just may bring her one step closer to finding her father. Will she and Daniel get married? Or will the stress of the engagement break them apart forever? IF ONLY FOREVER is book #4 in a dazzling new romance series that will make you laugh, cry, keep you turning pages late into the night-and make you fall in love with romance all over again. Book #5 will be available soon. "A very well written novel, describing the struggle of a woman (Emily) to find her true identity. The author did an amazing job with the creation of the characters and her description of the environment. The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining." --Books and Movies Reviews, Roberto Mattos (re For Now and Forever)
Keywords: Romantika, romány pro ženy